An Early Cradle of Civilization: The Importance and Greatness of Oman Past - Al Said, Haitham bin Tariq (The Archeological Heritage of Oman : An Early Cradle of Arabian Civilization brought to the Forefront of Cultural Resource Management, 2012)
We have gathered here today in front of the most distinguished and representative international assembly to celebrate the elements of Oman’s Heritage that extends to several thousands years. During the four decades, and as a result of H.M. Qaboos bin Sa’id Al Sa’id has successfully brought Oman into modernity through many transformations. His leadership has developed and embrace modernity without altering the innermost fabrics of a nation rooted in a glorious past, largely undisclosed till recent times. In reaching this goal, the Ministry of Heritage and Culture has played the key role in the management of our heritage and identity. Since the opening of our borders to archaeology and related disciplines, literally hundreds of field operations have been conducted in collaboration with many of the major research institutions worldwide. The time elapsed since the earliest archaeological investigations in 1973 has witnessed an impressive development in understanding how civilization emerged to transform a land of scarcity into a flywheel of wealth. The results indicate that, contrary to other regions of the world that built their civilizations on kingship, bureaucracy and urbanism, in Oman and Arabia in general society was shaped by the bonds of tribal alliances that raised the architecture of complexity on a foundation of kinship relations. With the emergence of the Magan Civilization at the end of the 4th millennium BCE wealth was created by the establishment of oasis agriculture and by the taming of desert and ocean to serve the needs of subsistence and trade. The Ministry of Heritage and Culture of Oman is currently at a stage where substantial investment is taking place as exemplify by highly targeted research projects with outstanding national programs, that include the creation of the Oman National Museum, an upgrading of the Natural History Museum in the capital area, as well as the building of the Maritime History Museum in the coastal town of Sur. This Symposium presents the many directions undertaken by the Ministry to explore, promote and preserve the physical and intangible expressions of our heritage. In that context, I would like to convey my gratitude and appreciation to all those who have contributed and still do so in the management of Oman’s heritage.
Keywords: Antiquité -- Oman